IMPACT OF SEVOFLURANE AND DESFLURANE ON THE DEVELOPMENT OF POST-PERFUSION CARDIAC FAILURE IN MYOCARDIAL REVASCULIZATION SURGERY WITH CARDIOPULMONARY BYPASS - Yu. S. Polushin; N. S. Molchan; A. A. Zhloba; M. Yu. Shiganov; A. E. Kobak; A. A. Khryapa; I. V. Tretyakova (Вестник анестезиологии и реаниматологии, 2018)
Goal of the study: to compare the impact pf sevoflurane and desflurane on metabolism in myocardium when performing aortocoronary bypass with cardiopulmonary bypass. Materials and methods: 56 patients suffering from coronary disease and undergoing myocardial revasculization with cardiopulmonary bypass were divided into two groups as per the type of used anesthetic: the group where desflurane was used (DG, n=28) and the group where sevoflurane was used (SG, n=28). Groups were divided into subgroups basing on lactate/pyruvate ratio (LPR) before aortic compression. The following rates of hemodynamic profile were registered (cardiac index, systolic output index, index of peripheral resistance and pulmonary vessels resistance, index of systolic output of the left and right ventricles, pulmonary capillary wedge pressure), oxygen transportation, consumption and extraction co-efficient. During the first 24 hours of post-perfusion period the following rates were evaluated: frequency of post-perfusion cardiac failure development, need in inotropic support, duration of artificial pulmonary ventilation and stay in the intensive care department. The level of troponin I was tested in 12 and 24 hours. During cardiopulmonary bypass the blood samples were collected from coronary sinus before aortic compression, before release of clamps and in 30 minutes of reperfusion in order to evaluate the expression of anaerobic metabolism in myocardium as per the levels of lactate, pyruvate and LPR. Results: Analysis of hemodynamic profile and gas exchange rates showed no significant difference in the impact of these anesthetics on the investigated parameters in the pre- and post-perfusion periods. The frequency of development of post-perfusion cardiac failure, prompt management of its manifestations and changes in the markers of myocardial injury with the use of sevoflurane and desflurane were no significantly different. When sevoflurane was used during anoxia the patients with initially low LPR demonstrated the increase of LPR in coronary sinus due to the increase of lactate (р < 0.05). When desflurane was used, both lactate and pyruvate went up thus LPR remained on the initial level. After release of clamps from aorta LPR levels were compared when both anesthetics were used as well as the relevant levels of lactate and pyruvate. Conclusion: The investigated anesthetics have similar impact on hemodynamics and possess similar cardio-protective action. However they might have different ways of its implementation.